Kid website assessment using knowledge discovery - Noordin, Mohamad Fauzan; A. Ali, Muna; Nassr, Rasheed (Center for Promoting Ideas (CPI), 2012)
Knowledge management and discovery play great role in business to improve the quality of information and help decision making process to issue accurate decision. However; those tools may employed in interest safety for kids, families need to verify whether specific kid website is an appropriate and helpful for kids. The main challenge of those tools is how to scan content. This paper tries to investigates the features that suppose to be available in the website to be suitable for kids, those features will be used in proposed framework that is may used to assess suitability and usefulness of the website for kids.